The dissemination of modernist Mahua literature, 1959-1989 / Chiah Seng - Chiah, Seng (2017)
This is a qualitative study and the subject is Mahua Modern Literature. Specifically, the study aims to analyse the strategies and methods employed by literary media in disseminating the Modernist Mahua Literature. The researcher has identified evidence which shows that the literary magazine Chao Foon Monthly, the Sirius Poetical Society and literati such as Bai Yao, Chen Ruixian and Wen Renping are the three main media vital in the dissemination of Modernist Mahua Literature. Research findings indicate that Mahua Literature has become a major component in the World Chinese Literature, and the emergence of Mahua Modernist Literature was the result of the influence by Modern Literature from Mainland China and Taiwan. The literary magazine Chao Foon Monthly is considered as one of the important media in promoting the emergence and development of Mahua Modernist Literature. It has employed various strategies to introduce and bring in the modernist resources from the West and Taiwan. It has finally changed the literary taste of local writers and readers, and also nurtured a big number of modernist writers. In the 1970s, the Sirius Poetical Society played an important part in promoting and strengthening Mahua Modernist Literature by publishing three representative anthologies of modernist poems and many other personal collections of different genres. It has thus enriched the publication of Mahua Modernist Literature. As for literati, Bai Yao was the pioneer in promoting and disseminating the modernist literature. He had written several articles to promote literary revolution and published the first modernist poem in Mahua literary arena. His footsteps were followed by Chen Ruixian, a modernist writer from Singapore, who joined the editorial board of Chao Foon Monthly and published various special issues to introduce Western modernist literature, modernist writers and the translations of modernist articles. During his term as the editor of Chao Foon Monthly from August 1969 to December 1974, he had supplied abundant resources to local writers and readers, thus improving the writing techniques of writers and consequently nurturing many Mahua modernist writers. The third literati Wen Renping on the other hand started disseminating the concept of modernism, the theories of modernist poetry and prose by publishing modernist poems, modernist prose and literary criticism in the 1970s. His poems and prose have proven that the use of modernist techniques is appropriate. It is very pertinent to recall here that Mahua Modernist Literature would have faced many difficulties without Chao Foon Monthly and its achievement would not have been as outstanding as what we have today. Similarly, without the Sirius Poetical Society, the three representative anthologies of Mahua modernist poems would not be published. Last but not least, the three literati Bai Yao, Chen Ruixian and Wen Renping have played active roles in disseminating Modernist Mahua Literature. In conclusion, the strategies employed by the three different media in disseminating Modernist Mahua Literature from 1950s to 1980s were successful.